Implementation of the diagnostic capabilities of the CMOS sensor in the NIR environment, using 1070 nm interference filter and a conventional IR-pass filters set. - Triolo, Paolo A.M. (Journal of Cultural Heritage, 2024)
• Optimization of the use of basic infrared systems for imaging analysis applied to cultural heritage. New diagnostic capabilities to conventional CMOS devices using interferencial filters coupled to conventional IR pass filter. This methodology gains better results in the study of underdrawing, pentimenti and artistic technique. This methodology provides more detailed recognition of azurite in false colours technique. Better IR image interpretation by art historians or conservators, through affordable, easy to use and portable equipment. NIR reflectography with silicon sensors (CMOS) is commonly acquired with 780 nm band-pass filters that allow the acquisition of clear images and high shutter speeds, while maintaining a low equipment cost. In this way, however, acquisition between 1000 nm and 1150nm-where the silicon sensor is still formally infrared sensitive-is in fact overhelmed by the stronger sensitivity in the infrared spectrum portion between 780 nm and 980 nm. Coupling a 1070 nm (± 5 nm) interferencial filter to an 87C nm IR pass filter (FHWH 850 nm) acquisitions in this portion of the NIR spectrum were carried out, witnessing a outstanding increase in visibility of underdrawings and pentimenti. A practical test of the effectiveness of the filters system mounted on the Nikon D800 IRUV was made, comparing the results with those obtained by the "Osiris" InGaAs detector by Opus Instruments. The comparison was performed on the "Deposition" (oil on panel) by Antonio Semino (1485–1555) in the collection of the Accademia Ligustica of Genoa, highlighting a significant qualitative proximity between the results obtained with the interference system and those with InGaAs detector, compared to the conventional acquisition with single IR long-pass filter. In addition, the 1070nm+87C filter system was used to increase the recognition capability of azurite pigments. This procedure widens the possibilities of first-impact diagnostics by means of low-cost and market available imaging systems based on commercial CMOS IRUV cameras..